Women's Community Center shaping and empowering lives - Rivera, Katrina C. (College of Architecture, University of the Philippines Diliman, 2018)
The city proper of Olongapo, Zambales is the area of study for this comprehensive project. Olongapo is a highly urbanized city and was once a US Naval Base during the WWII. The turnover of ownership to the Philippines was in 1991 after the eruption of Mt. Pinatubo. Olongapo and the naval base was left devastated but through the efforts of the local government and volunteers, the city reclaimed and developed the former US Naval Base. With a collective effort, they transformed it into what we know now as Subic Bay Freeport Zone. Olongapo prides itself with its good governance, great economic development, and its people, called the "Gapo." Although Olongapo prides itself as a model city in the Philippines, the city is also known for its infamous red-light district. A stark contrast from Olongapo's successful image as an HUC is the existence of red-light districts within the city. The existence of red-light district in the city of Olongapo is rooted in the demand of the main client of these areas which is the US Navy and the poverty that plagues the lower strata of the residents in the city. The women of Olongapo are more inclined to enter prostitution than men because of the gender inequality that makes them more likely to experience discrimination and poverty. Currently, the famous red-light district along Magsaysay Drive that is now a wholesome family night entertainment area have moved to Kalapandayan. It is an area in Brgy. Barretto just off the coast of Subic Bay that is lined with bars, brothels, and motels operating from noon to dawn. Given the current situation of prostitution in Olongapo, one would realize the decline of the sex industry in the area leaving the prostitutes paralyzed in a system that discriminates against women and the poor. The women of the red district are projected to soon lose the familiar form of income that is prostitution. To aid in the ensuing unproductivity of these women, there is a need for an intervention in their lifestyle to realize new opportunities and their full potential that isn't grounded on selling their bodies. The Women's Community Center shall shape and empower the lives of the women involved in prostitution through a community that builds trust and genuine relationships, facilitating holistic healing, providing a safe place to live, and job opportunities through education and training. With this facility, the women of the night are shaped, empowered, and illuminated into becoming women with the community.